2021
DOI: 10.3389/fpls.2021.765645
|View full text |Cite
|
Sign up to set email alerts
|

Deployment of Brassica carinata A. Braun Derived Brassica juncea (L.) Czern. Lines for Improving Heterosis and Water Use Efficiency Under Water Deficit Stress Conditions

Abstract: Among Brassica species, Ethiopian mustard (Brassica carinata A. Braun) is known to tolerate most abiotic stresses, including drought. Drought caused by low and erratic rainfall in semi-arid regions consistently challenges rapeseed mustard productivity. Development of B. carinata-derived lines (CDLs) in Brassica juncea (L.) Czern. nuclear background, carrying genomic segments from B. carinata, are expected to tolerate moisture deficit stress conditions. The present study was, thus, aimed to establish the phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The study aims to quantify the effects of stress on phenological traits development and yield loss. The delayed sowing and restricted irrigation are efficient strategies to identify heat-and drought-tolerant genotypes in a number of crops like bread wheat (Qaseem et al, 2019;Hussain et al, 2021;Yashavanthakumar et al, 2021), Durum wheat (Aberkane et al, 2021;Ayed et al, 2021;Laddomada et al, 2021), mustard (Limbalkar et al, 2021), lentil (Sellami et al, 2021;El haddad Devasirvatham et al, 2015). The results demonstrated that high temperature coupled with water stress is more destructive to the plant development process and, finally, reflected in yield reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The study aims to quantify the effects of stress on phenological traits development and yield loss. The delayed sowing and restricted irrigation are efficient strategies to identify heat-and drought-tolerant genotypes in a number of crops like bread wheat (Qaseem et al, 2019;Hussain et al, 2021;Yashavanthakumar et al, 2021), Durum wheat (Aberkane et al, 2021;Ayed et al, 2021;Laddomada et al, 2021), mustard (Limbalkar et al, 2021), lentil (Sellami et al, 2021;El haddad Devasirvatham et al, 2015). The results demonstrated that high temperature coupled with water stress is more destructive to the plant development process and, finally, reflected in yield reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Interspecific hybridization proved to be the most prominent approach for expanding the genetic variation in cultivated cultivars of diploid and polyploid species [10,24]. Among Brassicas, B. carinata is well suited for broadening the genetic base of other Brassicas since it is highly resistant to biotic [20] and abiotic [14,23] stresses. Genetic background plays an important role in the expression of heterosis [25]; therefore, the development of ILs in improved genetic backgrounds is desired.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interspecific hybridization was used at the Indian Council of Agricultural Research-Indian Agricultural Research Institute (ICAR-IARI), New Delhi to enrich the genome of B. juncea with favorable adaptive alleles of B. carinata, resulting in the development of morphologically and cytogenetically stable B. carinata-derived B. juncea ILs (2n = 18II). Using these lines, we have successfully demonstrated higher yield heterosis and drought tolerance in a set of 105 hybrids [23]. These outcomes have further encouraged us to identify heterotic genomic segments and dissect the responsive genes in B. carinataderived B. juncea ILs.…”
Section: Introductionmentioning
confidence: 90%
“…B. carinata (BBCC) is a suitable donor for improving environmental resilience and disease resistance in the high-yielding cultivars of B. napus (AACC) and B. juncea (AABB) through interspecific hybridizations (Limbalkar et al ., 2021; Raman et al ., 2017). The possibility of introgressions is higher in B. juncea as it shares the B genome with B. carinata and the A and C genomes have a higher propensity for recombination with each other than with the B genome (Attia et al ., 1987; Mason et al ., 2010; Struss et al ., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…campestris ) (Sharma et al ., 2016; Taylor et al ., 2002; Tonguç et al ., 2003; Vicente et al ., 2002), Alternaria leaf blight ( Alternaria brassicae ) (Krishnia et al ., 2000), white leaf spot ( Neopseudocercosporella capsellae ) (Gunasinghe et al ., 2016), and Sclerotinia stem rot ( Sclerotinia sclerotiorum ) (Navabi et al ., 2010b; Uloth et al ., 2016a). B. carinata is also tolerant to abiotic stresses such as drought, and heavy metal stress (Enjalbert et al ., 2013; Limbalkar et al ., 2021; Malik, 1990; Pan et al ., 2012; Wei et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%